Joining the New Band: Factors Triggering the Intentions of Malaysian College and University Students to Adopt 4G Broadband - Soon, Wong Lai; ., Bobby Chai Boon Hui; ., Wong Kee Luen (Information Management and Business Review, 2013)
The constantly intensifying demand for mobility has generated enormous market opportunities for telecom companies. The Internet has transformed lives of the Homo sapiens over the last decade in manners beyond the horizons of imaginations. 4G; the new kid on the block is the abbreviation for fourth-generation wireless; the phase of mobile communications providing high quality connections for transportable devices. By drawing on the attributes of the Technology Acceptance Model (TAM) which is an established methodology in technology based product acceptance researches; this paper contemplates the factors that influence the intentions of Malaysian college and university students to adopt 4G broadband for academic and for pleasure purposes. A theoretical framework has been proposed for this study which consisting of four independent variables, namely Perceived Ease of Use, Perceived Usefulness, Subjective Normand Perceived Enjoyment. The dependent variable of this study is Intention to Use.